2016
DOI: 10.1111/jvh.12623
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir versus tenofovir plus entecavir for chronic hepatitis B with lamivudine resistance and entecavir resistance

Abstract: We compared the viral suppressive efficacy of tenofovir disoproxil fumarate (TDF) mono-rescue therapy (TDF group) and TDF plus entecavir (ETV) combination-rescue therapy (TDF + ETV group) in chronic hepatitis B (CHB) patients with lamivudine resistance and entecavir resistance. One hundred and thirty-three CHB patients with lamivudine and entecavir resistance were investigated. Ninety-six patients were treated with TDF and 37 with TDF + ETV for at least 6 months. We compared the virologic response rate (HBV DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In our study, the cumulative VR rates in patients with HBV DNA levels ≥ 5.61 log 10 IU/mL (n=19) and those with HBV DNA levels < 5.61 log 10 IU/mL (n=54) were 22.7% and 77.9% at 12 months and 73.2% and 98.2% at 24 months, respectively. This observation is in agreement with two previous studies in CHB patients with resistance to both LAM and ETV [ 21 , 22 ]. Switching to TDF during the early stage of ETV resistance was significantly more effective in suppressing HBV DNA than delayed rescue therapy after HBV DNA increased to higher levels.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study, the cumulative VR rates in patients with HBV DNA levels ≥ 5.61 log 10 IU/mL (n=19) and those with HBV DNA levels < 5.61 log 10 IU/mL (n=54) were 22.7% and 77.9% at 12 months and 73.2% and 98.2% at 24 months, respectively. This observation is in agreement with two previous studies in CHB patients with resistance to both LAM and ETV [ 21 , 22 ]. Switching to TDF during the early stage of ETV resistance was significantly more effective in suppressing HBV DNA than delayed rescue therapy after HBV DNA increased to higher levels.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, treatment efficacy of TDF based combination or TDF monotherapy was not statistically different on pre-existing HBV resistant strains or exposure to other antiviral agents (ETV+ADV salvage treatment prior to TDF based rescue therapy). Thus, our studies confirmed that, compared to TDF monotherapy, TDF combination therapy did not provide any additional suppressive effect for CHB patients with resistance to LAM and ETV, which is in consistent with a few results previously reported [ 17 , 21 , 22 ]. However, a systemically designed trial with a large number of patients is needed to evaluate the efficacy of antiviral treatment strategy in CHB patients with multidrug resistance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…An even better response rate to TDF + LMV therapy in LMV-resistant patients was reported from a multi-centre study in Korea, where 92.6% of the LMV-resistant patients achieved <20 IU/ml of HBV DNA load after ~3 months of combination therapy8. Another recent study depicted that 85.4% of Korean CHB patients with LMV and ETV resistance achieved virologic response (HBV DNA level <20 IU/mL) following 24 months of TDF mono-rescue therapy21. The salvage potential of TDF was also evaluated in HBV genotype C infected Japanese patients who had failed treatment with other NAs.…”
Section: Discussionmentioning
confidence: 94%